Factors Associated with Work Stress Risk Among Crew Members of the Kelud Ship at Belawan Port in 2025 - Hendry, Baringin; Donal Nababan; Henny Arwina Bangun; Lukman Hakim; Jasmen Manurung (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Work stress is a state of tension that arises due to an imbalance between physical and psychological demands. Factors contributing to work stress include both job-related and individual factors. This study aims to analyze the factors associated with the risk of work stress among crew members of the Kelud Ship at Belawan Port in 2025. The study used a descriptive analytic design with a cross-sectional approach. The research was conducted from July 2024 to March 2025. The sampling technique used was accidental sampling, involving 50 crew members of the Kelud Ship at Belawan Port. The results showed significant relationships between age (p=0.035), physical work environment (p=0.001), workload (p=0.005), salary or wages (p=0.001), and interpersonal relationships (p=0.000) with the risk of work stress. The most dominant factor influencing work stress risk was workload. Therefore, it is recommended that the management of the Kelud Ship organize crew activities more efficiently, manage working and rest times appropriately to prevent fatigue, implement fair task rotations to avoid monotony, and maintain a balanced workload. Additionally, fostering open communication between the crew, captain, and management is essential to reduce misunderstandings and create a more harmonious working environment that promotes mutual support among crew members.